Evaluation of the DigiBete App, a Self-Management App for Type 1 Diabetes: Experiences of Young People, Families, and Healthcare Professionals - Nicky Kime; Steve Zwolinsky; Andy Pringle (MDPI AG, 2023)
Type 1 diabetes (T1DM) is a public health issue for children, young people, and families (CYPF) and requires innovative interventions. The DigiBete app is a self-management and educational app to help CYPF and healthcare professionals (HCPs) manage T1DM, featuring educational advice and resources such as guidance, quizzes, and educational and instructional videos on how to manage T1DM. To assess the impact and implementation of the app, the service-level evaluation deployed a mixed-methods design. App data were captured via the DigiBete platform and an online survey with a non-probability sample of HCPs (N = 178) and CYPF (N = 1165) = 1343. Overall, 55.7% (n = 512/919) of app users were female, and 4855 videos were viewed across the participating areas, with an average of 1213 videos per site (range 776-1679) and 4.4 videos per app user. The most popular videos were how to give a glucagon injection and "My Sick Day Rules", which showed what to do when CYPF were unwell due to T1DM. Interviews (n = 63) were undertaken with 38 CYPF and 25 HCPs. The findings indicate that CYPF and HCPs found the app an essential tool in the management of T1DM. CYPF and HCPs felt the app provided a valuable educational resource in a central location that was invaluable in an emergency or unknown situation. The app was a trusted and bona-fide source of information that could be accessed at any time. HCPs validated DigiBete in helping CYPF to manage their T1DM. At the same time, the app saved HCPs' service time and money and helped CYPF take back some of the control in managing their diabetes.